Transfer-Free In Situ CCVD Grown Nanocrystalline Graphene for Sub-PPMV Ammonia Detection. (1st January 2018) - Noll, Dennis; Hönicke, Philipp; Kayser, Yves; Wagner, Stefan; Beckhoff, Burkhard; Schwalke, Udo
Abstract : Reasonably-priced devices for the detection of toxic species in the atmosphere are critical for reasons of health. Previous research work shows the promising detection capabilities of graphene. Thus, we demonstrate the gaseous response of our nanocrystalline graphene field-effect transistors that can be fabricated hundredfold on a two inch substrate by our transfer-free in situ catalytic chemical vapor deposition process. By means of Raman spectroscopy and near edge X-ray absorption fine structure nanocrystallinity of the CCVD grown graphene films within the devices can be confirmed. Using a self-constructed vacuum probing station the sensitivity of the fabricated devices is extracted from dynamic electrical sampling measurements. With respect to ammonia it is found that the sensitivity is being higher than previously reported from other groups. Moreover, a comparable responsivity is achieved. A deeper understanding of the origin of the high sensitivity, which we attribute to the nanocrystallinity, is given by backgate input characteristics under varying ammonia concentration as well as from comparison with literature results on carbon nanotube gas sensors. Furthermore, the origin and influence of ammonia on the hysteresis of our nanocrystalline graphene field-effect transistors is discussed.